Women in contemporary politics in the Republic of Tuva and the Republic of Kalmykia (based on a sociological study) - Natsak, Organa D.; Badmaeva, Nogan V. (The New Research of Tuva, 2022)
The aim of the research was to study gender differences in Russian regional policy in the cases of the republics of Tuva and Kalmykia. The data for the analysis consist of active rolls of the officials working in government agencies in the republics as well as the results of a sociological study conducted there in January — March 2022. The latter was pursued through in-depth and expert interviews and dealt with the issue of perception of women’s role and potential in regional politics and government. The expert interviewees comprised public and political figures of different times. We analyzed the existing gender stereotypes, assessments of women’s potential in regional politics as well as a comparison of men’s and women’s positions. An analysis of the composition of the leadership staff of the legislative bodies of the two regions, the highest bodies of executive power, and ministries has found out that the number of active female politicians is quite small. Some regional features have been revealed: in Tuva, women are more represented in the parliament, while in Kalmykia, there are more women in the government of the region. Despite the high socioeconomic activity of women, a higher level of their education and, in general, their numerical predominance, patriarchal views on the role of females in politics and gender stereotypes are quite strong in both republics. According to these social biases, politics is a male sphere. In addition to the gender stereotypes in the regions under consideration, there are strong economic and sociopsychological barriers to women. They prevent females from being more active in regional politics. A common feature of public opinion in the two republics is that many people are unprepared for the fact that women can hypothetically lead the regions. At the same time, the political potential of females is estimated to be higher in Kalmykia than in Tuva. This fact was confirmed when a woman was appointed the Chairman of the Government of the Republic of Kalmykia in September 2022. An analysis of statements of female respondents has shown that women are ready to “sacrifice” their careers, including political ones, for the sake of the family, and statements of male respondents confirm the patriarchal nature of Tuvan and Kalmyk societies.